A Review of Barriers to Healthy Eating in Rural and Urban Adults - Jill R. Reed; Bernice C. Yates; Julia Houfek; Wayne Briner; Kendra K. Schmid; Carol Pullen (Rural Nurse Organization; Binghamton University, 2016)
Background: People encounter a variety of barriers that impact their ability to eat a healthy diet. Because of the higher obesity rates and poorer health status in rural adults, attention is needed on examining the gaps in knowledge about healthy eating barriers in rural adults. Purpose:  The purpose of this manuscript was to describe what is known about barriers to healthy eating in both rural and urban adults.  The social ecological model was used as a framework using individual, interpersonal, organizational, and community factors to organize barriers to healthy eating.  Methods:  Forty-two studies were found that discussed barriers to healthy eating in adults. Of these, 14 were conducted solely in rural settings, 2 in mixed rural and urban settings and the remaining 26 studies done in urban settings.  Results:  The impact of barriers unique to rural settings is not well understood as the majority of studies found were conducted in urban settings.  Barriers that rural adults face that may contribute to their greater occurrence of obesity were higher cost of healthy foods, lack of time, lack of social support, work issues and lack of access to grocery stores.  Conclusion:  More research is needed to provide a greater understanding of the unique challenges rural people face and how to eliminate barriers to maintaining a healthy diet.  Keywords:  barriers, healthy eating, rural, obesity DOI:  http://dx.doi.org/10.14574/ojrnhc.v16i1.379